Peran Dakwah Dalam Membangun Moralitas Generasi Milenial - Ririn Gusti; Arsyadani Mishbahuddin; Citra Dwi Palenti (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This article aims to analyze the role of Islamic da'wah in building the morality of the millennial generation through literature review methods. The millennial generation faces various moral challenges in the era of globalization and technology, such as the rapid flow of information and the diversity of values that often create confusion in determining the direction of life. Islamic da'wah has a strategic role in guiding this generation by instilling Islamic moral values which include honesty, responsibility, compassion, and justice. This article also discusses the unique characteristics of millennials, including their familiarity with technology, love of freedom, and critical tendencies. Relevant da'wah strategies include the use of digital media, humanist approaches, community formation, and the presentation of relevant role models. The results of the study show that creative and inclusive Islamic da'wah can increase spiritual awareness, strengthen positive values, help face moral dilemmas, and build a harmonious community. With this approach, Islamic da'wah not only forms moral individuals but also creates a peaceful and prosperous society.